2013
DOI: 10.1371/journal.pone.0072382
|View full text |Cite
|
Sign up to set email alerts
|

Are There Gender Differences in Coronary Artery Disease? The Malaysian National Cardiovascular Disease Database – Percutaneous Coronary Intervention (NCVD-PCI) Registry

Abstract: ObjectivesTo assess whether gender differences exist in the clinical presentation, angiographic severity, management and outcomes in patients with coronary artery disease (CAD).MethodsThe study comprised of 1,961 women and 8,593 men who underwent percutaneous coronary intervention (PCI) and were included in the Malaysian NCVD-PCI Registry from 2007–2009. Significant stenosis was defined as ≥70% stenosis in at least one of the epicardial vessels.ResultsWomen were significantly older and had significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…The findings showed that 64.9% of the participants were men, significantly higher than female. The finding was supported by a (Lee et al, 2013). In terms of ethnicity, a majority of the participants enrolled in this study were Malay (37.2%).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The findings showed that 64.9% of the participants were men, significantly higher than female. The finding was supported by a (Lee et al, 2013). In terms of ethnicity, a majority of the participants enrolled in this study were Malay (37.2%).…”
Section: Discussionsupporting
confidence: 71%
“…The findings showed that 64.9% of the participants were men, significantly higher than female. The finding was supported by a study done in Malaysia in which the findings revealed that a majority of the CAD patients in Malaysia were male (81.4%), with the total number of 8593 (Lee et al., ). In terms of ethnicity, a majority of the participants enrolled in this study were Malay (37.2%).…”
Section: Discussionmentioning
confidence: 64%
“…There is special interest in studying this association in older women who are at higher cardiovascular risk after the age of 60 years 15 and who present elevated cholesterol levels 7 and a higher incidence of diabetes 16 when compared to men. Although the muscle phenotypes studied were not significantly correlated with glucose (r = 0.243 for strength; r = 0.215 for MQ), basal insulin (r = 0.379 for strength; r = 0.284 for MQ) or insulin resistance (r = 0.364 for strength; r = 0.282 for MQ), there is interest in the study of the relationship between these phenotypes and markers of glucose uptake since skeletal muscle is the main site of glucose uptake in the body 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The identification of this correlation is particularly important for the elderly population because of the deleterious effects of aging on both the muscle system 12 and on the levels of some cardiometabolic risk markers 5,6 . The study of muscle phenotypes and blood variables related to cardiometabolic risk in older women is of special interest since women are at higher cardiovascular risk after the age of 60 years 15 and present elevated cholesterol levels 7 and a higher incidence of diabetes 16 when compared to men. In this respect, the establishment of a relationship between MQ and metabolic variables may contribute to clinical evaluation and to the identification of inflammatory conditions, alterations in glycemic control and other situations of increased cardiometabolic risk.…”
Section: Introductionmentioning
confidence: 99%
“…with CAD have a worse outcome than their male counterparts when no adjustments are made for other characteristics and comorbidities. 5,6 Although females tend to present with CAD later in life, the outcome can be severe. 6 Even when they present young, they tend to receive less evidence-based treatment than their male counterparts.…”
mentioning
confidence: 99%